The history of ethical regulation of biomedical research in the CIS member states - O. I. Kubar; G. L. Mkrtichyan; A. E. Nikitina; E. U. Vladimirova; L. A. Pynchenkova (Izdatelstvo OKI, 2018)
The history of development the ethical and legislative tools for regulation the biomedical research in the states-members of Commonwealth of Independent States (CIS) in the frame of the close collaboration the Forum for Ethics Committees in the Commonwealth of Independent States (FECCIS) and Inter-Parliamentary Assembly CIS (IPA CIS) is demonstrated in this article. The collaboration between FECCIS and IPA CIS stands on the unique experience of IPA CIS in the building of the new, humanistic legislation in the field of health care and on the initiatives of FECCIS to create a single legal space inside and outside of the CIS region. The necessity to promote the dignity, rights, and well-being of human participants in health research was the real reason for creation the Model Law «On the Protection of Human Rights and Dignity in Biomedical Research in the CIS». The process of the law creation, its direction, structure, compliance with international ethical standards and implementation in the local legislation of CIS states are analysed by the main authors of Model Law «On the Protection of Human Rights and Dignity in Biomedical Research in the CIS» and presented in this review.